2007
DOI: 10.1103/physrevd.75.101701
|View full text |Cite
|
Sign up to set email alerts
|

Critical flavor number in the three dimensional Thirring model

Abstract: We present results of a Monte Carlo simulation of the three dimensional Thirring model with the number of fermion flavors N f varied between 2 and 18. By identifying the lattice coupling at which the chiral condensate peaks, simulations are be performed at couplings g 2 (N f ) corresponding to the strong coupling limit of the continuum theory. The chiral symmetry restoring phase transition is studied as N f is increased, and the critical number of flavors estimated as N f c = 6.6(1). The critical exponents mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
115
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(132 citation statements)
references
References 26 publications
17
115
0
Order By: Relevance
“…By contrast, in the DSE studies [24,25] an essential scaling behavior of the Kosterlitz-Thouless type has been found, that is to say, a phase transition of infinite order. As argued in [31], the nature of the transition in these studies appears to depend on whether the strong-coupling limit is taken before or after N f N cr f . The scaling analysis on the lattice [31,32] is consistent with a power-law behavior corresponding to a secondorder phase transition which qualitatively confirms, but quantitatively deviates from the Kondo scenario [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, in the DSE studies [24,25] an essential scaling behavior of the Kosterlitz-Thouless type has been found, that is to say, a phase transition of infinite order. As argued in [31], the nature of the transition in these studies appears to depend on whether the strong-coupling limit is taken before or after N f N cr f . The scaling analysis on the lattice [31,32] is consistent with a power-law behavior corresponding to a secondorder phase transition which qualitatively confirms, but quantitatively deviates from the Kondo scenario [26].…”
Section: Introductionmentioning
confidence: 99%
“…By constructing an effective potential for the chiral order parameter, up to leading order of the 1/N f expansion N cr f = 2 has been found [26]. Extensive Monte Carlo simulations point to N cr f 6.6 [31]. The true value of N cr f is of decisive relevance for the applicability of such relativistic fermion effective theories for condensed matter systems, where the number of flavors is typically N f = 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, this is only an extrapolation of our leading-order result to finite N. Nevertheless, it is quite interesting that N crit is close to the real-world value of N = 4. (For comparison, for the Lorentz-invariant Thirring model the critical number of four-component Dirac fermions is quoted as 6.6(1) [10], to be compared with N crit /2 ≈ 2.) Due to the limitation of our calculations, we cannot determine whether the exact N crit is smaller or larger than 4.…”
Section: B Wavefunction Renormalizationmentioning
confidence: 99%
“…2 would be needed to distinguish these two possibilities unambiguously. Another route would be to perform a "biased bilayer" study for a related 2 + 1d theory, the Thirring model [17], whose behavior as a function of N f and μ is qualitatively similar to the model here [18], but whose continuum action is manifestly covariant implying a t ≡ a s throughout.…”
Section: Discussionmentioning
confidence: 99%